Interaction between ticlopidine or warfarin or cardioaspirin with ahighly standardized deterpened Ginkgo biloba extract (VR456) in ratand human - Di Pierro, F.; Rinaldi, F.; Lucarelli et al., M. (Acta Biomedica Atenei Parmensis, 2011)
Ginkgo biloba is available in Europe as an over-the-counter drug and it is reported to cause hemorrhage when co-administered with other anti-platelet agents. We set out to study the interactions of ticlopidine with Ginkgo biloba extract or VR456, a new highly standardized deterpened extract from Ginkgo biloba leaves. Male Wistar rats were used to study the effects of ticlopidine (50-100 mg/kg/day), given alone and in combination for 5 days with Ginkgo biloba extract (50 mg/kg/day) or VR456 (50 mg/kg/day), on bleeding time and ex vivo ADP-induced platelet aggregation measurements. In addition, human studies were performed with the compounds under investigation. Combined treatment of ticlopidine and undeterpened Ginkgo biloba extract increased anti-platelet effect and prolonged the bleeding time in the rat. On the contrary, the combination treatment of ticlopidine and VR456 increased anti-platelet effect but did not prolong bleeding time. Moreover, daily administration of 360 mg of VR456 for 14 days to ticlopidine-treated humans did not highlight any unwanted effect and did not alter PT/INR and PTT parameters. Same results have been also obtained in warfarin or in cardioaspirin-treated patients. These data point out the clear role played by the terpenoid, PAF-antagonist fraction of Ginkgo biloba extract in affecting bleeding risk in anticoagulant-treated subjects and suggest VR456 as a possible option treatment in geriatric people subjected to anticoagulant treatment where the use of standard Ginkgo biloba extracts are discouraged.